Long-term follow-up and outcome of phenylketonuria patients on sapropterin: a retrospective study - Keil, Stefanie; Anjema, Karen; Spronsen, Francjan J. van; Lambruschini, Nilo; Burlina, Alberto; Bélanger-Quintana, Amaya; Couce, Maria L.; Feillet, Francois; Cerone, Roberto; Lotz-Havla, Amelie S.; Muntau, Ania C.; Bosch, Annet M.; et al. (Pediatrics, 2013)
OBJECTIVE: Sapropterin dihydrochloride, the synthetic form of 6R-tetrahydrobiopterin (BH4), is an approved drug for the treatment of patients with BH4-responsive phenylketonuria (PKU). The purpose of this study was to assess genotypes and data on the long-term effects of BH4/sapropterin on metabolic control and patient-related outcomes in 6 large European countries. - METHODS: A questionnaire was developed to assess phenotype, genotype, blood phenylalanine (Phe) levels, Phe tolerance, quality of life, mood changes, and adherence to diet in PKU patients from 16 medical centers. - RESULTS: One hundred forty-seven patients, of whom 41.9% had mild hyperphenylalaninemia, 50.7% mild PKU, and 7.4% classic PKU, were followed up over ≤12 years. A total of 85 different genotypes were reported. With the exception of two splice variants, all of the most common mutations were reported to be associated with substantial residual Phe hydroxylase activity. Median Phe tolerance increased 3.9 times with BH4/sapropterin therapy, compared with dietary treatment, and median Phe blood concentrations were within the therapeutic range in all patients. Compared with diet alone, improvement in quality of life was reported in 49.6% of patients, improvement in adherence to diet was reported in 47% of patients, and improvement in adherence to treatment was reported in 63.3% of patients. No severe adverse events were reported. - CONCLUSIONS: Our data document a long-term beneficial effect of orally administered BH4/sapropterin in responsive PKU patients by improving the metabolic control, increasing daily tolerance for dietary Phe intake, and for some, by improving dietary adherence and quality of life. Patient genotypes help in predicting BH4 responsiveness.
Gesehen am 23.04.2021